2023
DOI: 10.1101/2023.03.03.530952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequence-based prediction of the solubility of peptides containing non-natural amino acids

Abstract: Non-natural amino acids are increasingly used as building blocks in the development of peptide-based drugs, as they expand the available chemical space to tailor function, half-life and other key properties. However, while the chemical space of modified amino acids (mAAs) is potentially vast, experimental methods for measuring the developability properties of mAA-containing peptides are expensive and time consuming. To facilitate developability programs through computational methods, we present CamSol-PTM, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…The comparison of the SASA of the whole structure of the two Aβ42 filaments types with respect to the SASA of the Aβ42 monomer in solution (41) indicates that the hydrophobic region in the C-terminus region of the protein (37)(38)(39)(40)(41)(42) is not exposed to the solvent in type I filaments (Figure 3A), generating a more soluble filament (Figure 4A), according to the structurally-corrected CamSol solubility score (42,43). Instead in the type II filaments it remains exposed to the solvent (Figure 3B), generating a more insoluble filament (Figure 4B, red box).…”
Section: Influence Of the Fuzzy Coat On The Solubility Scores Of Type...mentioning
confidence: 99%
“…The comparison of the SASA of the whole structure of the two Aβ42 filaments types with respect to the SASA of the Aβ42 monomer in solution (41) indicates that the hydrophobic region in the C-terminus region of the protein (37)(38)(39)(40)(41)(42) is not exposed to the solvent in type I filaments (Figure 3A), generating a more soluble filament (Figure 4A), according to the structurally-corrected CamSol solubility score (42,43). Instead in the type II filaments it remains exposed to the solvent (Figure 3B), generating a more insoluble filament (Figure 4B, red box).…”
Section: Influence Of the Fuzzy Coat On The Solubility Scores Of Type...mentioning
confidence: 99%
“…1a, b). The residues for substitution were selected based on their hydrophobicity to increase their intracellular solubility to improve functionalization [30,31]. Furthermore, the substitution of Aib within peptides has been previously demonstrated to promote and stabilize helical structures due to the additional dimethyl group integrated as part of the peptide backbone; our previous research has also demonstrated that such substitutions have also worked efficiently at improving the translocation of substituted peptides through the translocase of the outer membrane (TOM) complex in plant cells [19].…”
Section: Physical Characterization Of Cytcox and Cytaibmentioning
confidence: 99%
“…[13] Such efforts have led to novel structure/activity studies on modified peptides that present chemoinformatics tools to efficiently characterize the chemical space of these new peptides and thereby better understand their activities, e.g., their antimicrobial activity against multidrug-resistant bacteria. [14] In the context of the lipophilicity for non-canonical amino acids, prominent examples highlighting the significance and relevance of this topic include recent studies by Kubyshkin (2021) [15] and Oeller et al (2023). [16] The computational work of Oeller et al introduced the CamSol-PTM tool, which offers a rapid and accurate methodology for predicting the solubility of peptides containing non-standard amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In the context of the lipophilicity for non-canonical amino acids, prominent examples highlighting the significance and relevance of this topic include recent studies by Kubyshkin (2021) [15] and Oeller et al (2023). [16] The computational work of Oeller et al introduced the CamSol-PTM tool, which offers a rapid and accurate methodology for predicting the solubility of peptides containing non-standard amino acids. Regarding to the experimental work of Kubyshkin, it aimed to develop an experimental lipophilicity https://doi.org/10.26434/chemrxiv-2024-8smwg ORCID: https://orcid.org/0000-0003-4029-4528 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%